Optimalisasi Strategi Memelihara Manajemen Waktu Untuk Mencapai Keseimbangan Hidup Pada Santri Pondok Pesantren - Septiowati, Rini; Habibah, Habibah; Tanjung, Asridah Warni (Forum Kerjasama Pendidikan Tinggi, 2026)
The Community Service (PKM) entitled Time Management Strategy for Students at the RH La Tahzan Foundation in Cinangka, Depok – West Java aims to implement and maintain time management strategies for students to optimize their busy daily activities in the Islamic boarding school environment. The activity methods include observation, questionnaire distribution, counseling, time management technique training, and mentoring in implementing the strategies for two to three weeks. The strategies introduced include time blocking, the 3P priority technique (Important–Necessary–Supporting), the use of timers, the Pomodoro technique, and daily evaluations. The results of the activity showed a significant increase in the efficiency of students' time use, such as reduced transition time, increased focus on night study, and the formation of a habit of making daily plans. In addition, students also experienced increased discipline, the ability to complete assignments on time, and a decrease in academic stress levels. However, several challenges were still encountered, such as inconsistent schedule implementation and peer influence. Overall, the target of this service was the students of the RH La Tahzan Foundation, Cinangka, Depok – West Java. The results of this PKM demonstrate that simple yet structured time management strategies can help students maintain a more effective daily rhythm. Sustainable implementation is expected to improve students' independence, academic achievement, and quality of life at the Islamic boarding school, extending this knowledge back home, into the surrounding environment, and into the community.